A Theory of International Crisis Lending and IMF Conditionality - Zettelmeyer, Jeromin; Jeanne, Olivier; Ostry, Jonathan (Washington, D.C. : International Monetary Fund, 2008)
We present a framework that clarifies the financial role of the IMF, the rationale for conditionality, and the conditions under which IMF-induced moral hazard can arise. In the model, traditional conditionality commits country authorities to undertake crisis resolution efforts, facilitating the return of private capital, and ensuring repayment to the IMF. Nonetheless, moral hazard can arise if there are crisis externalities across countries (contagion) or if country authorities discount crisis costs too much relative to the national social optimum, or both. Moral hazard can be avoided by making IMF lending conditional on crisis prevention efforts-"ex ante" conditionality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet